Electrochemical and thermal characteristics of prismatic lithium-ion battery based on a three-dimensional electrochemical-thermal coupled model. (October 2021) - Li, Huanhuan; Saini, Ashwani; Liu, Chengyang; Yang, Jufeng; Wang, Yaping; Yang, Tao; Pan, Chaofeng; Chen, Long; Jiang, Haobin
Highlights: 3D electrochemical-thermal average coupled model is developed for 30 Ah NCM LIB. Model uses two sets of geometry models, unit cell geometry and battery geometry. Effect of 4 parameters on electrochemical and thermal characteristics has studied. Results are analyzed on the 1D and 3D scales. Abstract: The performance of large-size lithium-ion batteries (LIBs) is significantly affected by the internal electrochemical processes and thermal characteristics which cannot be obtained by the experimental methods directly. In this work, a 3D electrochemical-thermal coupled model is developed for 30 Ah ternary cathode LIB by coupling 3D layered electrochemical model and 3D thermal model. This coupled model is further validated by comparing simulation results with experimental values, showing the good performance of a developed model. The internal electrochemical processes and thermal characteristics, such as current density, heat generation rate and temperature distribution inside the LIB for 1D and 3D scales, of the battery are investigated at different discharge rates and ambient temperatures. It is observed that the reduction in both the discharge capacity and voltage occurred at high discharge rate and low temperature due to high polarization and transport resistance. A 3D layered model indicated the close relation between current density distribution and total heat generation rate distribution in the unit cell. Among total heat generation at low discharge rate, mostly contribution comes from the heat generated in a negative electrode while the proportion of heat generation in other components increases gradually with the discharge rate, especially in a positive electrode. Also, the effect of battery thickness and heat transfer coefficient are studied. The results show that the temperature gradients along the battery thickness and width are significantly higher for thickened battery and larger heat transfer coefficient, which causes heat inhomogeneities during the electrochemical processes. The proposed model can be used to optimize the electrode and structural design for developing better battery thermal management systems and safer batteries. Graphical abstract: Image, graphical abstract